Toll-Like Receptor Agonists as Adjuvants for Allergen Immunotherapy - Kirtland, Max E.; Tsitoura, Daphne C.; Durham, Stephen R.; Shamji, Mohamed H. (Frontiers in Immunology, 2020)
Toll-like receptors (TLRs) are essential components of innate immunity and provide defensive inflammatory responses to invading pathogens. Located within the plasma membranes of cells and also intracellular endosomes, TLRs can detect a range of pathogen associated molecular patterns from bacteria, viruses and fungi. TLR activation on dendritic cells can propagate to an adaptive immune response, making them attractive targets for the development of both prophylactic and therapeutic vaccines. In contrast to conventional adjuvants such as aluminium salts, TLR agonists have a clear immunomodulatory profile that favours anti-allergic T lymphocyte responses. Consequently, the potential use of TLRs as adjuvants in Allergen Immunotherapy (AIT) for allergic rhinitis and asthma remains of great interest. Allergic Rhinitis is a Th2-driven, IgE-mediated disease that occurs in atopic individuals in response to exposure to otherwise harmless aeroallergens such as pollens, house dust mite and animal dander. AIT is indicated in subjects with allergic rhinitis whose symptoms are inadequately controlled by antihistamines and nasal corticosteroids. Unlike anti-allergic drugs, AIT is disease-modifying and may induce long-term disease remission through mechanisms involving upregulation of IgG and IgG4 antibodies, induction of regulatory T and B cells, and immune deviation in favour of Th1 responses that are maintained after treatment discontinuation. This process takes up to three years however, highlighting an unmet need for a more efficacious therapy with faster onset. Agonists targeting different TLRs to treat allergy are at different stages of development. Synthetic TLR4, and TLR9 agonists have progressed to clinical trials, while TLR2, TLR5 and TLR7 agonists been shown to have potent anti-allergic effects in human in vitro experiments and in vivo in animal studies. The anti-allergic properties of TLRs are broadly characterised by a combination of enhanced Th1 deviation, regulatory responses and induction of blocking antibodies. While promising, a durable effect in larger clinical trials is yet to be observed and further long-term studies and comparative trials with conventional AIT are required before TLR adjuvants can be considered for inclusion in AIT. Here we critically evaluate experimental and clinical studies investigating TLRs and discuss their potential role in the future of AIT.